2021
DOI: 10.1017/jfm.2020.1182
|View full text |Cite
|
Sign up to set email alerts
|

Minimal multi-scale dynamics of near-wall turbulence

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
104
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(147 citation statements)
references
References 65 publications
(140 reference statements)
39
104
4
Order By: Relevance
“…It is therefore hoped that the GQL approximation offers a new perspective for these issues, while confirming the previous findings obtained by 'non-intrusive' analysis (e.g. Cho et al 2018;Doohan et al 2021).…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…It is therefore hoped that the GQL approximation offers a new perspective for these issues, while confirming the previous findings obtained by 'non-intrusive' analysis (e.g. Cho et al 2018;Doohan et al 2021).…”
Section: Introductionsupporting
confidence: 86%
“…λ z ≈ 57η, where η is the Kolmogorov scale). Finally, the turbulent transport spectra are weakly positive in the region very close to the wall (y + < 10) over a wide range of the spanwise wavelength scales (200δ ν λ z 1h) and this is due to an inverse energy transfer from small to large scales (Cho et al 2018;Doohan et al 2021).…”
Section: Spectral Energy Transfermentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, the observations made for transition in the present study offer some important outlooks for the relevance of the Orr mechanism to fully-developed turbulent flow. The existence of the Orr mechanism has repeatedly been reported by several previous studies [61][62][63][64]. These studies are primarily concerned with the generation of wall-normal velocity structure via the Orr mechanism in relation to the self-sustaining process of the energy-containing eddies (or coherent structures) in wall-bounded turbulence [53,[65][66][67].…”
Section: Discussionmentioning
confidence: 69%
“…These studies are primarily concerned with the generation of wall-normal velocity structure via the Orr mechanism in relation to the self-sustaining process of the energy-containing eddies (or coherent structures) in wall-bounded turbulence [53,[65][66][67]. However, the precise role and origin of the Orr mechanism in fully-developed turbulence are still matters of debate: it was initially proposed that the Orr mechanism is a part of the self-sustaining process at a given length scale for the generation of the wall-normal velocity structure [61][62][63], but a recent study showed that the Orr mechanism can well be initiated by the wall-normal velocity structure originating from the energy cascade of 'larger' energy-containing eddies [64]. In any case, it should be pointed out that all these investigations ignore the amplification of the spanwise velocity structures caused by the lift-up effect following the Orr mechanism.…”
Section: Discussionmentioning
confidence: 99%